Stabilisation of soft clay slurry with CSA-OPC blends for land reclamation - Tan, Jasper Wei Heng (2019)
In Singapore, land is seen as one of the most scarce resources. Hence, over the years, the government has been extensively expanding its land area through land reclamation. Land reclamation requires a large amount of fill materials, and with the lack of granular fill materials, an alternative would be to use dredged soft clay slurry. However, soft clay slurry has high compressibility and low shear strength due to its high water content. Therefore, it needs to be treated for land reclamation. The aim of the report is to study the effectiveness of using Calcium sulfoaluminate-Ordinary Portland Cement (CSA-OPC) blends as binders in the stabilisation of the soft clay slurry. The experiments were carried out using a range of CSA-OPC blends to stabilise soft clay slurry. All of the specimens were cured in batches of 7, 28 and 56 days, and measured for bulk density, water content, dry density as well as unconfined compressive strength. In addition, scanning electron microscope (SEM) and x-ray diffraction (XRD) were also executed to analyse the microstructure and mineralogy of the CSA-OPC treated soft clay slurry. The results indicated that substituting 10%-30% OPC with CSA can considerably increase the strength of stabilised clay slurry up to 50%; however, excessive substitution will decrease the strength. Also, these stabilised samples showed a high percentage in strength gain when cured from 7-28 days, while this percentage started to decrease when cured for 56 days. The optimum substitution percentage varies with total binder content, and the optimum values in this study are 30% and 20% for binder contents of 60kg/m³ and 80 kg/m³, respectively.